The Effect of Family Economic Education towards Lifestyle Mediated By Financial Literacy - Theodora, Berta Dian; Marti’ah, Siti (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to know the student’s lifestyle whether it is influenced by education that has been accepted in family or their financial literacy. Samples were 334 out of 2040 students of Indraprasta PGRI University, Jakarta. Technique of data analysis used path analysis. Findings show that 60.78% of students are in the middle category for economic education in family, 47% of students are in the high category for financial literacy and 58% of students have a high lifestyle. Economic education influences the lifestyle by 6.4% and financial literacy affects on lifestyle by 3.7%. The influence of family education through financial literacy toward lifestyle is 1.9%. Therefore, it can be concluded that financial literacy does not increase the influence of education Economy in family to lifestyle. Then, the results of the research will be used as one of the reference in the application of entrepreneurship lectures.